Awareness, attitude and ethical concern of dental practitioners about stem cells: a cross-sectional study - Bahabri, Rayan; Taymour, Nevine; Ali, Mawadh; Alahmadi, Ghada; Mandorah, Ayman; Borzangy, Sary (Brazilian Dental Science, 2021)
Objective:     To evaluate the level of awareness and attitude among dental practitioners regarding the use of stem cells in dentistry and to determine their knowledge of ethical concerns related to the recent therapy. Material and Methods: A cross-sectional survey-based study was conducted at Taibah University Dental College and Hospital. Medina and at governmental and private dental clinics at the western region of Saudi Arabia. Responses of dental practitioners who completed the survey were recorded between March 2019 and July 2019 without containing any personal identifiers. Level of awareness and attitude and knowledge about ethical issues in relation to stem cell therapy was established. Results: A total of 214 male and female dental practitioners participated in this study and the majority were registered at the Saudi Commission for Health Specialists 128 (59.8%). Dental consultants reported the highest percentage of awareness about dental stem cells (96%, p= 0.005), whereas general dental practitioners (56.2%, p= 0.005) and specialists (52%, p= 0.005), respectively had a lower percentage. When ethical concerns were determined, dental consultants had the highest percentage of knowledge (56%, p= 0.005), whereas dental practitioners (71.2%, p= 0.005) with < 5 years of experience (69.1, p= 0.002) lacked information about related ethical issues. Conclusion: Ways to increase stem cell awareness among dental practitioners in this study recommended including stem cell topics in the dental curriculum and organizing frequent seminars and conferences on this subject. KeywordsStem cell; Awareness; Ethical; Dental practitioner.